Orange fibre effects on nutrient digestibility, fermentation products in faeces and digesta mean retention time in dogs - Volpe, Lara Mantovani [UNESP]; Putarov, Thaila Cristina [UNESP]; Ikuma, Caroline Tiemi [UNESP]; Eugênio, Débora Alberici [UNESP]; Ribeiro, Priscila Martins [UNESP]; Theodoro, Stephanie [UNESP]; Scarpim, Lucas Bassi [UNESP]; Pacheco, Peterson Dante Gavasso [UNESP]; Carciofi, Aulus Cavalieri [UNESP] (Taylor & Francis, 2021)
Fermentable fibres are used in commercial dog food to promote intestinal health by providing substrates for better metabolic activity of the gut microbiota. Brazil is the world’s largest producer of oranges, from which it is possible to obtain fibre with a relevant soluble fraction. The present study compared the effects of two inclusions of orange fibre (1% and 3%, on as fed basis) with a negative control (without addition of fibre source) and two positive controls, beet pulp (3%) and purified inulin (1%), totalling five extruded diets for dogs. The experiment followed a randomised block design with 4 blocks of 10 dogs, 2 dogs per food in each block, totalling 8 dogs per diet. The apparent total tract nutrient digestibility was determined by total faecal collection. Faecal pH and fermentation product content were also measured. The digesta mean retention time (DMRT) was evaluated using plastic markers. The inclusion of a 3% fibre source in diets with 3% orange fibre and beet pulp reduced DM, OM, and energy digestibility (p < 0.05). Diets with 3% orange fibre, beet pulp and 1% inulin presented lower crude protein digestibility than the control (p < 0.05). Dietary fibre digestibility was higher for orange fibre-supplemented diets than inulin (p < 0.05). Beet pulp and 3% orange fibre inclusions resulted in increased moisture content in the faeces of dogs (p < 0.05) but did not alter DMRT. Total short-chain fatty acids were higher than the control in the faeces of dogs fed both orange fibre levels and the beet pulp-supplemented diet (p < 0.05), and the inulin diet-fed dogs presented intermediate values. Butyrate was higher in the faeces of dogs fed the diets supplemented with 1% and 3% orange fibre (p < 0.05), and similar values to the control were observed for beet pulp- and inulin-fed animals. Thus, it was concluded that orange fibre presented higher apparent total tract dietary fibre digestibility than beet pulp and had a fermentation profile in the colon that promoted the generation of butyrate, an effect not observed for inulin and beet pulp.
Keywords: Beet pulp; butyrate; extrusion; inulin; soluble fibre